Free Radical Scavenging Activity of Riceberry and Pathum Thani Rice Extracts for Developing Face Powder - Senajuk, Watchara; Phasuk, Sasamol; Nilsang, Poonyanuch; Takolpuckdee, Pannraphat (Journal of Food Health and Bioenvironmental Science, 2023)
Thai rice today is not limited to staple food, but it has been transformed into a variety of medicinal and beauty products, as part of a growing industry with a bright future. We measured total phenolic content, total flavonoid content, free radical scavenging activity, lycopene, β-carotene, color and SPF of raw materials in face powder. Riceberry extract sample contained phenolic and flavonoid with the highest level at 26.46±0.008 mg GAE/g of extract and 101.63±0.034 mg Rutin/g of extract. Free radical scavenging activity was measured by DPPH assay: the Riceberry extract sample contained antioxidants that indicated the EC50 at 108.31±0.024 μg/mL. All raw materials showed SPF, which could be used as foundation data for making face powder. However, wood apple powder has the highest SPF for a material, that can be used as a raw material, for further development of face powder.